2013
DOI: 10.1007/s11095-013-1117-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Organic Anion Transporting Polypeptide 1B3 in Cancer Cell Lines

Abstract: Ct-OATP1B3 is capable of transporting its substrates into cancer cells. Its mRNA expression is regulated by DNA methylation-dependent gene silencing involving MBD2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 32 publications
2
39
1
Order By: Relevance
“…Similarly, Nagai et al reported that lung, colon, and pancreatic cancer tissues and cell lines express an alternative OATP1B3 transcript (72). However, this study proposed the four potential ORFs resulting in much shorter amino acid sequences than the ORF reported by our laboratory and another subsequent report (71,100). Currently, csOATP1B3 is found to be the major isoform expressed only in cancer cells, but not in normal tissues.…”
Section: Oatp1b3 (Gene Symbol Slco1b3)mentioning
confidence: 49%
See 2 more Smart Citations
“…Similarly, Nagai et al reported that lung, colon, and pancreatic cancer tissues and cell lines express an alternative OATP1B3 transcript (72). However, this study proposed the four potential ORFs resulting in much shorter amino acid sequences than the ORF reported by our laboratory and another subsequent report (71,100). Currently, csOATP1B3 is found to be the major isoform expressed only in cancer cells, but not in normal tissues.…”
Section: Oatp1b3 (Gene Symbol Slco1b3)mentioning
confidence: 49%
“…With regard to the regulatory mechanisms for OATP1B3 expression, several investigations implicated the involvement of the liver-enriched transcription factor, hepatocyte nuclear factor 3β (HNF3β), as well as epigenetic and hypoxiamediated mechanisms (41,(100)(101)(102). The contribution of these reported mechanisms may vary depending on the tissue types and disease states.…”
Section: Oatp1b3 (Gene Symbol Slco1b3)mentioning
confidence: 99%
See 1 more Smart Citation
“…3) Development stage-dependent CYP2E1 expression is influenced by the methylation status of this gene. 4) Phase II genes including UGT1A1 , GSTP1 , SULT1A1 and genes for efflux transporters like MDR1, BCRP and members of the OATP family of uptake transporters are epigenetically regulated due to DNA methylation [86, 87, 89, 88]. …”
Section: Genetics Epigenetics and Interindividual Differences In Dmentioning
confidence: 99%
“…Several studies have shown that this gene is ectopically expressed in solid tumors of non-hepatic origin, particularly colon cancer [131134]. Investigations into the cause of this ectopic expression revealed that the normal liver-restricted promoter is silent in these cancers, with expression of “cancer-type” (Ct)-OATP1B3 being driven from an alternative promoter in the second canonical intron [133, 134]. While not previously reported as being within a TE, we noted that this alternative promoter maps within the 5’ LTR (LTR7) of a partly full-length antisense HERV-H element that is missing the 3’ LTR.…”
Section: Introductionmentioning
confidence: 99%